Kyrle’s disease in a child with autoimmune sclerosing cholangitis. - Gál, A.I.; Bar-Ilan, E.; Vass, V.; Veres, K.; Szalai, Z. (European Journal of Pediatric Dermatology, 2022)
Kyrle’s disease is also known as hyperkeratosis follicularis et parafollicularis in cutem penetrans and is classified as a subtype of acquired perforating dermatosis. Kyrle’s disease is extremely rare in children and is often associated with underlying chronic conditions, more typically kidney disease and diabetes mellitus, but also congestive heart failure, hyperlipidemia, infectious diseases such as HIV and liver failure. To date, only one clinical work has described an association between cquired perforating dermatosis and sclerosing cholangitis in an adult patient. The current report describes a case of Kyrle’s disease associated with sclerosing cholangitis in a 4-year-old girl.